2008
DOI: 10.1111/j.1740-8261.2008.00399.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasound, Computed Tomography, and Magnetic Resonance Imaging in Detection of Acute Wooden Foreign Bodies in the Canine Manus

Abstract: We evaluated the diagnostic sensitivity of ultrasound, nonenhanced computed tomography (CT) and nonenhanced magnetic resonance (MR) imaging in detecting wooden foreign bodies in the canine manus. Identical wooden splinters were manually inserted into 30 cadaver canine manus, and the limbs were evaluated using ultrasound, CT, and MR imaging by independent observers. All sites were rated as positive or negative for the presence of a foreign body, and observer certainty was scored on a 1-10 scale. Using receiver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
50
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 39 publications
4
50
0
2
Order By: Relevance
“…Yet, non‐enhanced CT was the most accurate modality for detection of wooden foreign bodies in a canine cadaveric model followed by ultrasound and MRI, respectively (Ober et al . ). The advantages of CT over MRI include (1) the possibility of choosing small‐thickness slices to obtain a large number of images of the scrutinised region (Tidwell & Jones ), thus providing a higher spatial resolution, MRI can indeed be of limited value for identification of small FBs (<2·5 mm) which are near the lower limit of detection of this imaging modality (Ober et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Yet, non‐enhanced CT was the most accurate modality for detection of wooden foreign bodies in a canine cadaveric model followed by ultrasound and MRI, respectively (Ober et al . ). The advantages of CT over MRI include (1) the possibility of choosing small‐thickness slices to obtain a large number of images of the scrutinised region (Tidwell & Jones ), thus providing a higher spatial resolution, MRI can indeed be of limited value for identification of small FBs (<2·5 mm) which are near the lower limit of detection of this imaging modality (Ober et al .…”
Section: Discussionmentioning
confidence: 97%
“…The advantages of CT over MRI include (1) the possibility of choosing small‐thickness slices to obtain a large number of images of the scrutinised region (Tidwell & Jones ), thus providing a higher spatial resolution, MRI can indeed be of limited value for identification of small FBs (<2·5 mm) which are near the lower limit of detection of this imaging modality (Ober et al . ); (2) continuous imaging through the thorax into the abdomen or vice versa , thus allowing RDTs to be closely scrutinised in both body cavities. This is very useful in the context of RDTs potentially related to a migrating FB which may cross the diaphragm; (3) acquisition of CT images is a much quicker process than MRI and subsequently requires shorter anaesthesia times for chronically compromised patients and finally (4) CT does not carry the risk associated with performing MRI examinations in patients with ferromagnetic FB.…”
Section: Discussionmentioning
confidence: 99%
“…They preferred MRI and US for detection of FBs as their first diagnostic modality (16). In 2008, Ober et al compared CT, MRI and US for detection of wooden FBs in the canine manus and reported CT as a more accurate modality than MRI and US (17). …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they may have internal striations or a 'target' shape in transverse images 3,15 . Computed tomography has been found to be more sensitive than ultrasound and MRI in detecting wooden foreign bodies in the manus 13 . In this study, a CT scan was conducted on Case 4 for research purposes due to suspected spirocercosis seen on thoracic radiographs.…”
Section: Discussionmentioning
confidence: 99%